INOVASI KBM MEDIA PERMAINAN ULAR TANGGA BERBASIS ETNOMATEMATIKA UNTUK MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Gunardi, Ari; Dzil Ikrom, Fadhli (Journal of Professional Elementary Education, 2024)
The method used is a qualitative research method. A research method that uses numerical data to test hypotheses, measure variables, analyze relationships between variables and answer research questions. In this method, data is collected systematically using standardized measurement instruments and the data is interpreted using statistical analysis. The purpose of quantitative research is to obtain data that can be measured and analyzed objectively and to make generalizations about the relationship between the variables studied. Research requires a method that is tailored to the problem and purpose of the research. In other words, the research method plays an important role in data collection and analysis. The purpose of this study is to describe the use of the "Snake and Ladder" game tool based on ethnic mathematics to improve students' problem-solving abilities. The researcher reviewed previous studies related to this study and the results of student research and found that the "Snake and Ladder" game tool can improve students' problem-solving abilities in mathematics. This study also helps students gain a deeper understanding of the material presented. Students' problem-solving abilities also affect their overall performance in mathematics. The teaching and learning process should not be monotonous and boring so that students can easily understand what they are learning.